Toward a Palestinian Critical Race Theory in Education - Najib, Amanda (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2026)
This paper explores the unique experiences of Palestinian Americans within the U.S. education system through the lens of Critical Race Theory (CRT). Addressing a gap in existing literature, the research question investigates how racialization, demonization, and structural racism shape the educational and social experiences of Palestinian Americans. Utilizing a qualitative analysis of legal documents, media reports, policy papers, and academic literature, the findings reveal pervasive racialization and demonization, significant structural barriers, and severe suppression of political activism. These findings suggest that Palestinian Americans face unique and multifaceted systemic challenges that are not adequately addressed by traditional CRT frameworks. The development of a Palestinian American Critical Race Theory (PalestinianCRT) is proposed to better understand and address these specific issues. This research is important as it broadens the scope of CRT and calls for targeted advocacy and reform to promote social justice and equity.